2013
DOI: 10.1002/14651858.cd003999.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Relapse prevention interventions for smoking cessation

Abstract: At the moment, there is insufficient evidence to support the use of any specific behavioural intervention to help smokers who have successfully quit for a short time to avoid relapse. The verdict is strongest for interventions focused on identifying and resolving tempting situations, as most studies were concerned with these. Little research is available regarding other behavioural approaches.Extended treatment with varenicline may prevent relapse. Extended treatment with bupropion is unlikely to have a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(102 citation statements)
references
References 125 publications
1
101
0
Order By: Relevance
“…28 Among those women who do quit during pregnancy, nearly all wish to remain abstinent after the birth of their baby; 43 however, the vast majority relapse within 12 months of the birth. 44,45 Much less is known about effective interventions to prevent postnatal relapse; 45 behavioural support has not been shown to be effective for preventing postnatal relapse and is offered by only a minority of UK SSSs. 45 Smoking in pregnancy and postnatal relapse rates therefore remain high, particularly for women living in disadvantaged circumstances, 46 suggesting that this group of smokers face particular social and economic barriers that may inhibit their ability to access support and/or to stop smoking.…”
Section: Smoking Cessation In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…28 Among those women who do quit during pregnancy, nearly all wish to remain abstinent after the birth of their baby; 43 however, the vast majority relapse within 12 months of the birth. 44,45 Much less is known about effective interventions to prevent postnatal relapse; 45 behavioural support has not been shown to be effective for preventing postnatal relapse and is offered by only a minority of UK SSSs. 45 Smoking in pregnancy and postnatal relapse rates therefore remain high, particularly for women living in disadvantaged circumstances, 46 suggesting that this group of smokers face particular social and economic barriers that may inhibit their ability to access support and/or to stop smoking.…”
Section: Smoking Cessation In Pregnancymentioning
confidence: 99%
“…44,45 Much less is known about effective interventions to prevent postnatal relapse; 45 behavioural support has not been shown to be effective for preventing postnatal relapse and is offered by only a minority of UK SSSs. 45 Smoking in pregnancy and postnatal relapse rates therefore remain high, particularly for women living in disadvantaged circumstances, 46 suggesting that this group of smokers face particular social and economic barriers that may inhibit their ability to access support and/or to stop smoking. Understanding these barriers (and facilitators) offers scope for identifying other ways of reducing smoking in pregnancy and supporting women to remain abstinent after childbirth.…”
Section: Smoking Cessation In Pregnancymentioning
confidence: 99%
“…However, behavioural approaches to relapse prevention studies with virtual methods, such as mobile phone and applications, are still in infancy 52 . Review of relapse prevention intervention suggested no long-term benefit of behavioural intervention but recommends extended pharmacological treatment intervention 53 . The dose-response relationship is demonstrated in randomized control trial of web-based computer tailored intervention 53,54 .…”
Section: Review Papermentioning
confidence: 99%
“…Review of relapse prevention intervention suggested no long-term benefit of behavioural intervention but recommends extended pharmacological treatment intervention 53 . The dose-response relationship is demonstrated in randomized control trial of web-based computer tailored intervention 53,54 . We assume low relapse rate in our study due to the influence of frequent feedback and interaction sharing features.…”
Section: Review Papermentioning
confidence: 99%
“…18 A Cochrane systematic review of trials of smoking relapse prevention found insufficient evidence to support the use of any specific intervention for preventing smoking relapse in short-term quitters. 19 The current smoking cessation guidelines do not recommend any specific interventions for smoking relapse prevention. 20,21 According to findings from a survey of smoking cessation professionals, the uncertain evidence base about effectiveness was an important barrier to the use of relapse prevention interventions in stop smoking practice.…”
Section: Interventions For Smoking Relapse Preventionmentioning
confidence: 99%